PENATAAN LINGKUNGAN PURA MUNCAK SARI DESA SANGKETAN, PENEBEL, TABANAN - I W. Sukerayasa; I. B. A. Swamardika; I W. A. Wijaya; I N. Surata; I N. Lanus; I N. Sutarja (Buletin Udayana Mengabdi, 2016)
Muncak Sari Luhur Temple is one of several temples located in West part of Batu Karu Sad Kahyangan Temple. The temple is within Sangketan village, district of Penebel, Tabanan region. Recently, it has been carried out a renovation and an extension of the temple, that cover the west part of “mandala” and around the Dalem Kahyangan temple. The building extention at west part of “mandala” was as large as 122.5 m2, with a length of 17.5m and a width of 7m. The designed concrete building is supported by 14 pillars. In addition to the building extention, an installation of lighting at west part of parking area was also carried out. The renovation and extension of the temple have incresed the comfortability of the people during the last temple ceremony.